Banner waste mixture: The impact on quality of traditional brick’s compressive strength - Maryana, Okky Fajar Tri; Ikhwanuddin, Rifqi; Anggini, Safitri; Barna, Ridho (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2020)
The regional election in Lampung province has finished. The events left the amount of ex-campaign props such as banner to become waste. The final landfills and the waste reuse system are still an unsolved issue in Lampung province. A study of materials composition is required to find potential reuse of the waste. One of the traditional products in Lampung province is conventional bricks. Previous studies show that mixing local clay with additional materials such as Rice Husk Ash (RHA) could improve its characteristics, especially water absorption potentiality. This study reported the prototype of bricks with banners waste mix produced employing a conventional method. The method obtains the best admixture composition is 0.002 kilograms banner waste/volume 0.125 liters or 0.02% total weight of clay-dough. The morphology of the prototype shows a similar texture with a non-waste mixture of traditional brick. It is burnt-clay red-bricks, which is used as a control in this study. The prototype bricks show smooth texture and nearly flat on all sides. The addition waste composition ratio of more than 0.002 kilograms indicated cracking texture that affects the market tend to buy bricks, which has good appearance and texture. This study also reported that the mixture's effect is decreasing compressive strength, almost 20% from the control sample.